Characterization of the Zirconium Metal-Organic Framework (MOF) UiO-66-NH2 for the Decomposition of Nerve Agents in Solid-State Conditions Using Phosphorus-31 Solid State-Magic Angle Spinning Nuclear Magnetic Resonance (31P SS-MAS NMR) and Gas Chromatography – Mass Spectrometry (GC-MS). (11th February 2021) - Jung, Hyunsook; Kim, Min-Kun; Lee, Juno; Kwon, Ji Hyun; Lee, Jaeheon
Abstract: UiO-66-NH2 was synthesized in situ and analyzed as a reactive sorbent for nerve agent removal in the solid-state environment. UiO-66-NH2 had the smallest pore sizes, centered at 7 Å with added pores at 13 and 15 Å, indicating a hierarchically microporous structure. The in situ reaction was examined using phosphorus-31 solid state-magic angle spinning nuclear magnetic resonance ( 31 P SS-MAS NMR) and further confirmed by gas chromatography – mass spectrometry (GC-MS). The results show that the nerve agents were decomposed via hydrolysis by UiO-66-NH2 and the overall rates were reduced for solid-phase reactions. Of the characterized components O -pinacolyl methylphosphonofluoridate (GD), N, N -dimethylphosphoramidocyanidate (GA), and O -ethyl S -diisopropylaminomethyl methylphosphonothioate (VX), GD was decomposed faster than GA and VX by UiO-66-NH2 . Specifically, GD was decomposed to O -pinacolyl-methylphosphonic acid (PMPA) with a half-life of approximately 430 min in the presence of neat UiO-66-NH2 . However, GA and VX were slowly hydrolyzed, forming reaction products such as ethylphosphate and dimethylphosphoramidic (DMPA) acid monoethylester from GA, and ethyl methylphosphonic acid (EMPA), methylphosphonic acid (MPA), and 2-(Diisopropylamino)ethyldisulfide (DES)2 from VX, respectively. This work describes the processes involved for these materials when they are deployed to protect against a nerve agent release, implying the practical application of UiO-66-NH2 for a broad range of filtration applications in the field.